Strengthening the Regulatory Sandbox as a Synergistic Effort for Investment Climate Growth in Artificial Intelligence Era - Jumantoro, Tegar Raffi Putra; Kusuma, Ajeng Pramesthy Hardiani; Putri Triana, Syafira Meylanie (Universitas Muhammadiyah Gresik, 2024)
The development of Artificial Intelligence (AI) has had a significant influence on various sectors of life, especially investment, which is marked by the rapid growth of Financial Technology (FinTech). Therefore, the regulatory sandbox program was born as an answer to the high rate of FinTech as a mechanism for testing products before they are marketed. In Indonesia itself, the institutions authorized to regulate regulatory sandboxes are Otoritas Jasa Keuangan (OJK) and Bank Indonesia. By using normative juridical methods, researchers conducted an analysis of statutory regulations, namely regulations of OJK and Bank Indonesia (BI) to obtain study results by looking at the effectiveness of regulations regarding regulatory sandboxes in Indonesia. Researchers attempt to provide a juridical comparison between the two institutional regulations. The data collection method was carried out using the library study method and reviewing various library sources. The results of this research show that the use of regulatory sandboxes is very important in investing in Indonesia. Apart from catching up with other countries, the use of a regulatory sandbox also guarantees the protection of consumer rights so that it can attract interest in investing. Researchers provide recommendations in the form of improving coordination between OJK and companies as well as providing adequate resources to facilitate the optimization of regulatory sandboxes in Indonesia. Apart from that, providing regular outreach to the public is very important to increase their understanding of the regulatory sandbox. The research results note that there are still several shortcomings in the use of regulatory sandboxes, such as the lack of accuracy of test results. With this research, it is hoped that several challenges and obstacles from the previous use of regulatory sandboxes can be evaluated by the authorized institutions.